Role of N-Arachidonoyl-Serotonin (AA-5-HT) in Sleep-Wake Cycle Architecture, Sleep Homeostasis, and Neurotransmitters Regulation - Murillo-Rodríguez, Eric; Di Marzo, Vincenzo; Machado, Sergio; Rocha, Nuno B.; Veras, André B.; Neto, Geraldo A. M.; Budde, Henning; Arias-Carrión, Oscar; Arankowsky-Sandoval, Gloria (Frontiers in Molecular Neuroscience, 2017)
The endocannabinoid system comprises several molecular entities such as endogenous ligands [anandamide (AEA) and 2-arachidonoylglycerol (2-AG)], receptors (CB1 and CB2), enzymes such as [fatty acid amide hydrolase (FAHH) and monoacylglycerol lipase (MAGL)], as well as the anandamide membrane transporter. Although the role of this complex neurobiological system in the sleep–wake cycle modulation has been studied, the contribution of the blocker of FAAH/transient receptor potential cation channel subfamily V member 1 (TRPV1), N-arachidonoyl-serotonin (AA-5-HT) in sleep has not been investigated. Thus, in the present study, varying doses of AA-5-HT (5, 10, or 20 mg/Kg, i.p.) injected at the beginning of the lights-on period of rats, caused no statistical changes in sleep patterns. However, similar pharmacological treatment given to animals at the beginning of the dark period decreased wakefulness (W) and increased slow wave sleep (SWS) as well as rapid eye movement sleep (REMS). Power spectra analysis of states of vigilance showed that injection of AA-5-HT during the lights-off period diminished alpha spectrum across alertness in a dose-dependent fashion. In opposition, delta power spectra was enhanced as well as theta spectrum, during SWS and REMS, respectively. Moreover, the highest dose of AA-5-HT decreased wake-related contents of neurotransmitters such as dopamine (DA), norepinephrine (NE), epinephrine (EP), serotonin (5-HT) whereas the levels of adenosine (AD) were enhanced. In addition, the sleep-inducing properties of AA-5-HT were confirmed since this compound blocked the increase in W caused by stimulants such as cannabidiol (CBD) or modafinil (MOD) during the lights-on period. Additionally, administration of AA-5-HT also prevented the enhancement in contents of DA, NE, EP, 5-HT and AD after CBD of MOD injection. Lastly, the role of AA-5-HT in sleep homeostasis was tested in animals that received either CBD or MOD after total sleep deprivation (TSD). The injection of CBD or MOD increased alertness during sleep rebound period after TSD. However, AA-5-HT blocked this effect by allowing animals to display an enhancement in sleep across sleep rebound period. Overall, our findings provide evidence that AA-5-HT is an important modulator of sleep, sleep homeostasis and neurotransmitter contents.